2012
DOI: 10.1024/0300-9831/a000099
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a 28-Day Oral Cyanocobalamin Supplementation on Vitamin B Status in Spanish Institutionalized Elderly

Abstract: A supplementation with an oral supplement solution of 500 µg cyanocobalamin daily for only four weeks, a shorter period than that found in former studies, may be considered suitable in institutionalized elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A study by Sanchez et al showed that a daily dose of 1.4 ug of vitamin B 12 was not sufficient to improve vitamin B 12 status [30]. Supplementation with higher doses of vitamin B 12 ( > 500 ug/day) have proven effective in Latino populations residing in USA [34] and institutionalized Spanish elderly increased significantly from 308.4 pmol/L to 558.3 pmol/L (p < 0.001) [35]. Also, Favrat et al showed that oral vitamin B 12 treatment normalized the metabolic markers [4].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Sanchez et al showed that a daily dose of 1.4 ug of vitamin B 12 was not sufficient to improve vitamin B 12 status [30]. Supplementation with higher doses of vitamin B 12 ( > 500 ug/day) have proven effective in Latino populations residing in USA [34] and institutionalized Spanish elderly increased significantly from 308.4 pmol/L to 558.3 pmol/L (p < 0.001) [35]. Also, Favrat et al showed that oral vitamin B 12 treatment normalized the metabolic markers [4].…”
Section: Discussionmentioning
confidence: 99%
“…There is a new trend to give oral and nasal preparations, and preliminary data suggest that they could be just as effective. [37][38][39] Although the possibility of erratic absorption needs to be considered, 40 oral and nasal routes could play a role in medical treatment after correction to normal levels, especially in those who need lifelong treatment. Care should be taken in the replacement of folate in people with a concomitant vitamin B 12 deficiency because the administration of folate without replacement of vitamin B 12 can worsen neurological sequelae.…”
Section: Long Answermentioning
confidence: 99%
“…It is thought to be due to either alteration in small bowel motility, which stimulates small bowel bacterial overgrowth and subsequent vitamin B12 deficiency, or by directly decreasing vitamin B12 absorption process. [10][11] Peripheral neuropathy is caused by both diabetes mellitus and vitamin B12 deficiency which may produce overlapping clinical pictures. However, non-diabetic neuropathies may be present in patients with diabetes and may be treatable with therapeutic vitamin B12 or vitamin B complex mixtures containing B12 supplementation. )…”
Section: Introductionmentioning
confidence: 99%